x + 8 = 25
x=17
3 + 10 x 4
43
8(4+2) = ?
48
2x + 8x=
10x
X - 3 = 10
X=13
How can you rewrite 92 in expanded form?
9 x 9
Simplify the following expression:
5(x - 3)
5x - 15
Simplify:
4x + 2x -8x
-2x
4x= 28
X=7
How can you rewrite the following in exponential form?
7 x 7 x 7 x 7 x 7
75
3 + 42 * (3 + 2)
83
7 + 9(2x - 3)
18x - 20
-3x + 2x +5 -2
-x + 3
x/8=5
X=40
62
2(3 +5) -6
-3(-x - 10)
3x + 30
Simplify:
-4x +2x -6 +3
-2x-3
Solve for X:
2x + 5 = 17
X=6
23 +32
17
12
6 + (-2 + -5)
-1
x + 10 - 6(x - 3x) + 4
13x + 14
Simplify:
-2(x + 4) + 5x
-8 + 3x